Building strong music programs : a handbook for preservice and novice music teachers - Ryan, Charlene, 1971-; MENC, the National Association for Music Education (U.S.) (Lanham, Md. : Rowman & Littlefield Education, 2009)
While program building is an essential, time-consuming part of every music teacher's job, students are rarely prepared for it. Ryan covers issues important to student teachers, new teachers, teachers changing schools, and teachers looking to rejuvenate their existing programs.
Your first job -- Friends and allies -- Students -- Performances -- Courses -- Publicity -- Final thoughts.
Includes bibliographical references.
"Published in partnership with MENC: The National Association for Music Education."
Keywords: Music -- Instruction and study